Efficacy and safety of Vismodegib treatment in patients with advanced basal cell carcinoma and multiple comorbidities. Issue 6 (30th October 2019) - Spallone, Giulia; Sollena, Pietro; Ventura, Alessandra; Fargnoli, Maria C.; Gutierrez, Carlota; Piccerillo, Alfredo; Tambone, Sara; Bianchi, Luca; Peris, Ketty
Abstract: Basal cell carcinoma (BCC) is the most common malignancy in Caucasians, and its incidence is increasing. Most BCCs are treated surgically, nevertheless surgery is not an effective treatment for locally advanced or metastatic BCC. Alterations in hedgehog signaling pathway, a key regulator of cell growth and differentiation during development, are implicated in the pathogenesis of basal‐cell carcinoma. Vismodegib is a small‐molecule inhibitor of smoothened (SMO), a key component of the hedgehog (Hh) signaling pathway, administered in BCC patients, especially when surgery and radiotherapy treatments have failed. We report a series of eight elderly patients treated with vismodegib for advanced BCC and affected by concomitant multiple comorbidities. The efficacy and tolerability of vismodegib in patients with single and/or multiple comorbidities has been poorly studied. In our observation an overall high safety and tolerability has been observed over the course of treatment, with side effects of grade I and II and no changes in vital parameters, electrocardiography and echocardiogram. Vismodegib has been shown to be a safe and well tolerated treatment option for elderly patients affected by multiple comorbidities and advanced BCC.